RETURNS OF ASSETS IN CORRUPTION CRIMINAL ACTS AS ALTERNATIVE RESTORING STATE LOSSES - Komang Ekayana (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2020)
Corrupted state assets certainly hurt the country narrowly, but also broadly where it harms the country and its people. However, the formal approach through the current criminal procedure law has not been able to recover the losses suffered by the state. In fact, state losses resulting from corruption are state assets that must be saved. Then there needs to be a new breakthrough to recover state losses through the asset recovery model. When looking at the country from the perspective of the victims, the state must obtain protection, in this case recovery from the losses suffered due to corruption. This paper examines the model of returning assets resulting from corruption in the law enforcement process that focuses on the rule of law in the 2003 UNCAC Convention and the mechanism of returning state assets in terms of Law No. 20 of 2001 concerning amendments to Law No. 31 of 1999 concerning Eradication of Corruption Crimes.